Design of determinants of online shopping intentions and behavior of students at private universities in East Jakarta 2024 - Ependi, Ependi; Mujanah, Siti; Budiarti, Endah (Edelweiss Applied Science and Technology, 2024)
Globalization and technological advances, especially the internet, have changed people's shopping patterns. Online shopping is now a trend, allowing easy access to products at any time. The Covid-19 pandemic has accelerated this transition, with 74.5% of consumers preferring to shop online rather than offline, creating a new profitable consumption pattern. This study aims to identify significant relationships between latent variables that influence online shopping behavior, including Online Shopping Motivation, Subjective Norms, Perceived Behavioral Control, Consumer Knowledge, Online Shopping Intention, and Online Shopping Behavior. This research design uses a quantitative approach with SEM-PLS to analyze the relationship between variables that influence online shopping behavior of students at Private Universities in East Jakarta, providing an in-depth understanding for e-commerce in more effective marketing strategies. The results of the analysis show that Perceived Behavioral Control plays an important role in increasing online shopping knowledge and intention, supporting the theory of Planned Behavior. In addition, Subjective Norms are proven to influence consumer knowledge and intention, reflecting the impact of the social environment on shopping decisions. Although there is a positive relationship between Online Shopping Intention and Online Shopping Behavior, the results show that intentions are not always realized in action, indicating the complexity of consumer behavior. The implications of this study include the importance of consumer education to increase perceived control, leveraging social norms in marketing strategies through collaboration with influencers, and attention to other factors that influence shopping decisions. This study highlights the need to develop more effective marketing strategies, based on a deeper understanding of the relationships between variables, to increase consumer engagement and conversion on online shopping platforms. These findings contribute to academic and practical understanding in the context of shopping behavior in the digital era.